Report from the conference ”Application of the Succession Regulation in the EU Member States”, Katowice 12 September 2019 - Pacuła, Krzysztof (Problemy Prawa Prywatnego Międzynarodowego, 2020)
On 12 September 2019, the premises of the Faculty of Law and Administration of the University of Silesia in Katowice (Poland) witnessed one of such events, which will arguably go down in history of private international law in Poland. On that day, the University hosted an international conference on the Regulation (EU) No 650/2012 of 4 July 2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of succession and on the creation of a European Certificate of Succession (“the Succession Regulation”), and on the various issues relating to the succession matters within the European area of freedom, security and justice.